EVALUATION OF ANTIMICROBIAL ACTIVITY OF WATERY AND ALCOHOLIC EXTRACTS FOR ANCHUSA STRIGOSA ON GROWTH OF GRAM POSITIVE PATHOGENIC BACTERIA ISOLATED FROM PHARYNGITIS AND TONSILLITS CASES: HANAN A. AL-AYMI , AMINA N. AL-THAWANI, FARID J. AL-TAHAN - AL-AYMI, HANAN A. (The Iraqi Journal of Veterinary Medicine, 2007)
The effects of Anchusa strigosa plant extract were studied in respect totheir of gram positive bacterial growth inhibition. were isolated from cases ofpharyngitis and tonsillitis . alcoholic and hot water extracts of the plants as wellas their dried powders were prepared . The preliminary chemical tests revealedacidic pH of all extracts.The dried powder , watery and alcoholic extracts of A. strigosacontained resins ,tannins , phenols, flavonoids, glycosides and avery littleamount of alkaloids in its watery and alcoholic extract.The alcoholic extract ofA. strigosa showed more patent inhibitory effect on resistant bacteria than itswatery extract and the best effect was on growth of Strept.salivarius andStrept.pyogenes inhibition zone diameter 27.0,26.0 mm. In the present study ,the Minimum inhibitory concentration (MIC) and Minimum bacteriocidalconcentration (MBC) of the plants extracts were measured for the morepredominant gram positive isolates and the results varied according to differentkinds of plant extracts and different types of bacteria . The least values of MICand MBC were for alcoholic extract of A. strigosa on Staph.epidermidis whichvalued 10% ,20% respectively .It has been noticed that the watery extracts of A.strigosa , have a sedative effect when given dosing 5 g/kg for laboratorymice , these extracts however, showed a synergistic sedative effect when mixedwith pentobarbitone and caused prolongation of sleeping time in experimentalmice .Neither the alcoholic nor the watery extracts of the plants showed anytoxic effect on the laboratory mice after oral dosing of 2.5 – 15 g /Kg B.W.Watery and alcoholic extracts, Anchusa strigosa , Pharyngitis ,Tonsillitis .Pathogenic bacteria